If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 21 = 13x + 56 Reorder the terms: 21 + 6x = 13x + 56 Reorder the terms: 21 + 6x = 56 + 13x Solving 21 + 6x = 56 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 21 + 6x + -13x = 56 + 13x + -13x Combine like terms: 6x + -13x = -7x 21 + -7x = 56 + 13x + -13x Combine like terms: 13x + -13x = 0 21 + -7x = 56 + 0 21 + -7x = 56 Add '-21' to each side of the equation. 21 + -21 + -7x = 56 + -21 Combine like terms: 21 + -21 = 0 0 + -7x = 56 + -21 -7x = 56 + -21 Combine like terms: 56 + -21 = 35 -7x = 35 Divide each side by '-7'. x = -5 Simplifying x = -5
| 7x+13=10x-5 | | 2000000x^4=80000 | | 372=2L+176 | | (8+4)x^3+8= | | 2(x-12)=3(x+5) | | 7s+5=26 | | -7(4.5v-3.5)=27.5-5.5v | | 372=2L+88 | | x^4=.04 | | 3+4(2x-3)=7 | | 5+3(2x-7)=5+6x-21 | | 24a-48=18a-36 | | 8x^3+4x^3+8= | | y=1.03 | | -4x-10=4(5x-4) | | 5xy-3b=11 | | 4-9x=y | | f(5)=10 | | 10x-2=-4x+10 | | D-6pie=pie | | 6x+12=(-12) | | 7-4(d-30)=23 | | -6s+8.5+5.5s=24.5 | | 2(x^2+10-25)=0 | | 3g+4(-8+2g)=1g | | 45+x=(13+x)+(4+x)+(10+x) | | 5+12-1=0 | | 2x^2-8x+23=0 | | log^8(3x-9)=2 | | 2(x-12)=3(x+15) | | 4c-8=7c+7 | | 4.5+8.5(1-4k)=-25.5 |